Extending and Modifying LAMMPS Writing Your Own Source Code : A pragmatic guide to extending LAMMPS as per custom simulation requirements /: A pragmatic guide to extending LAMMPS as per custom simulation requirements. (2021) - Dr, Mubin, Shafat; Li, Jichen; Dr, Plimpton, Steven
No abstract available